Precautions in the management of opioid agonist therapy: from target population characteristics to new formulations and post-marketing monitoring - a focus on the Italian system - Guido Mannaioni; Fabio Lugoboni (BioExcel Publishing Ltd, 2023)
Opioid use disorder (OUD) is a serious medical condition with vast social, health and economic impact. Individuals with OUD are prescribed opioid agonist therapies, such as methadone, levomethadone, buprenorphine or naloxone/buprenorphine, to reduce the risks associated with illegal substance abuse, eventually leading to opioid use abstinence. The OUD population has peculiar frailties, mainly related to the psychiatric sphere, which may jeopardize their therapeutic course. Amongst the possible phenomena that may contribute to treatment failure, opioid agonist therapy misuse and diversion are of utmost importance, leading to serious repercussions for patients as well as for national health systems. To minimize the consequences related to these practices, it is necessary to implement cross-cutting precautions, from the formulation of abuse-deterrent drugs to the implementation of a national monitoring system that oversees the health situation and signals when action is needed. Based on these premises, this article focuses on data and insights concerning the Italian territory.